Exploring the role of family on the career development of Xhosa-speaking graduates - Madyaka, Anela (Department of Environmental and Geographical Science, 2022)
This study explored the role of family on the career development of Xhosa-speaking graduates in South Africa. There are multiple environmental and individual influences on career development. However, this study focused specifically on family. The Xhosa culture, like other African cultures, endorses cultural values of deference and strong familial connections with extended family. Data from fourteen semi-structured in-depth interviews were analysed using thematic analysis. The key themes that emerged were (1) cultural beliefs, (2) social support and (3) the notion of black tax. The findings suggested that there is a strong relation between a family's cultural beliefs, family responsibilities and the perceived social support on graduate's career development. The understanding of ‘western' career aspirations with familial cultural expectations and support in forming a coherent self-concept could be considered a significant challenge in the career development of these Xhosa graduates. The findings supported the familial influences on graduates' career development and contributed new insights on how family influence is perceived and maintained from an intersectional perspective. The implications for career development in diverse contexts are offered.